Rural Community Tourism: An Approach toward Sustainable Development Goals - Badal, Bharat Prasad (Nepalese Journal of Development and Rural Studies, 2018)
This paper highlights on Rural Community Tourism (RCT) that can be a new approach to achieve sustainable development goals (SDGs). However, United Nations Development Program and concerned government Agency has yet started working by linking two fundamental tools of Rural Development i.e., Rural Community Development and Rural Tourism. Therefore, to identify the linkages between such tools and for developing new RCT as new approach, the study has been conducted. Methodologically, this study applied library based method for data collection and comparative review analysis method for appraising research issues. Theoretically, this study look at on 17 SDGs and RCT both are developed based on the principles of sustainable development. This study comes up with conclusion that only RCT can link entire 17 sustainable goals with nominal investment. Hence, better to apply RCT, a new approach by federal governments (federation, provincial and local levels) as well as UN development agencies and I/NGOs while planning and implementing 17 SDGs related plans, programs and projects.